2015
DOI: 10.1073/pnas.1510754112
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent synaptic GRIP1 accumulation drives synaptic scaling up in response to action potential blockade

Abstract: Synaptic scaling is a form of homeostatic plasticity that stabilizes neuronal firing in response to changes in synapse number and strength. Scaling up in response to action-potential blockade is accomplished through increased synaptic accumulation of GluA2-containing AMPA receptors (AMPAR), but the receptor trafficking steps that drive this process remain largely obscure. Here, we show that the AMPAR-binding protein glutamate receptor-interacting protein-1 (GRIP1) is essential for regulated synaptic AMPAR accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 51 publications
7
67
4
Order By: Relevance
“…Many studies have confirmed this original result in vitro [6], as well as ex vivo in acute slices prepared from both juvenile and adult animals that had previously undergone in vivo deprivation [7][8][9][10][11][12][13][14]. Synaptic scaling does have layer-specific properties in cortex, where scaling in layer 4 is limited to early development [7], but layer 5 [12,15] and layer 2/3 [10] can scale throughout adulthood.…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 72%
“…Many studies have confirmed this original result in vitro [6], as well as ex vivo in acute slices prepared from both juvenile and adult animals that had previously undergone in vivo deprivation [7][8][9][10][11][12][13][14]. Synaptic scaling does have layer-specific properties in cortex, where scaling in layer 4 is limited to early development [7], but layer 5 [12,15] and layer 2/3 [10] can scale throughout adulthood.…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 72%
“…Several groups have postulated that fluctuations in intracellular Ca 2+ levels initially “sense” changes in activity (Ibata et al., 2008, Thiagarajan et al., 2005) that may be read out by changes in the activation of CaMKIV resulting in changes in gene expression (Ibata et al., 2008). In addition, the expression of scaling up is mediated by the accumulation of GluR2-containing receptors (Gainey et al., 2009, Gainey et al., 2015), likely driven by alterations with the glutamate receptor-interacting protein-1, GRIP-1 (Gainey et al., 2015), and protein-interacting-with C Kinase 1, PICK1 (Anggono et al., 2011). Other molecules implicated in various aspects of synaptic scaling include the neurotrophin brain-derived neurotrophic factor (BDNF) (Rutherford et al., 1998), the immediate early gene Arc (Shepherd et al., 2006), the cytokine TNFα (Steinmetz and Turrigiano, 2010, Stellwagen and Malenka, 2006), the immune molecule MHC1 (Goddard et al., 2007), β3 integrins (Cingolani et al., 2008), and the scaffold proteins PSD-95 and PSD-93 (Sun and Turrigiano, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, brain-derived neurotrophic factor (BDNF) is important for homeostatic upscaling; BDNF depletion resembles TTX-induced mEPSC amplitude upscaling. Additional factors that mediate upscaling include tumor necrosis factor alpha (TNFα), the C-kinase 1-interacting protein PICK1 and the glutamate receptor interacting protein GRIP1, and the immediate early gene Arc (Gainey et al, 2015; Tan et al, 2015; Turrigiano, 2012; Wang et al, 2012a). Further, homer1a and Eph4A receptor tyrosine kinase are important for neuronal activity-induced synaptic downscaling (Turrigiano, 2012).…”
Section: Introductionmentioning
confidence: 99%